Analysis of selected physical and performance attributes of the United States Olympic team handball players: Preliminary study - Bergemann, B. (The Sport Journal, 1999)
The purpose of this investigation was to construct a team handball test battery that would be reflective of the skills, abilities, physical fitness components and anthropometric factors that contribute to high levels of performance, and to establish a database of performances by the National Team Handball players. Additional purposes for developing the test included using the test to screen potential players at the National level, to provide teachers in the schools and colleges with tests that are inexpensive and easy to administer, and to provide self-administered tests that would train the athletes to improve their performance in team handball.